Refugee imaginaries : research across the humanities - Cox, Emma; Durrant, Sam, 1970-; Farrier, David, 1979-; Stonebridge, Lyndsey, 1965-; Woolley, Agnes (Edinburgh University Press, 2020)
Includes thirty-two newly written chapters on representations by and of refugees from leading researchers in the field, Refugee Imaginaries establishes the case for placing the study of the refugee at the centre of contemporary critical enquiry.